Analisis Kondisi Fisik Mahasiswa Penjaskesrek Universitas Nahdlatul Ulama Sulawesi Tenggara Angkatan 2023 - Iful, Edy Gunawan, Ika Sartika, Resky Ana Abadi, Suryani (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
This study aims to find out the physical condition of Unusra Physical Education Students. This research is a quantitative descriptive research. The sample withdrawal was selected in the research by purposive sampling, namely 30 students of the 2023 class of Physical Education Students. Data analysis technique using simple percentages. Based on the results of the study, data was obtained that the physical condition of Unusra Physical Education Students was that there were no students who had physical condition in the Special category, very good, less and less than once, there were 14 (46.67%) students in the good category, and as many as 16 (53.33%) students in the sufficient category, so it was concluded that the physical condition of students was not optimal.